COMPOSITION, VOLATILE COMPONENTS, AND TRACE ELEMENTS IN ANDESITIC MELTS OF THE KURILE-KAMCHATKA REGION - Tolstykh M.L.; Naumov V.B.; Babansky A.D. (My University, 2007)
Melt inclusions in minerals from some volcanoes of the Kurile-Kamchatka region were examined. The studied basaltic andesites and andesites were sampled from volcanoes of the Central Kamchatka depression (Shiveluch and Bezymyannyi), Eastern Kamchatka volcanic belt (Avachinskii and Karymskii), and Iturup Island, Southern Kuriles (Kudryavyi). Basalts of the 1996 eruption of the Karymskii volcanic center and dacites of Dikii Greben, volcano, Southern Kamchatka were also studied. More than 260 melt inclusions from 31 rock samples were homogenized, and quenched glasses were analyzed using electron and ion microprobes. The compositions of melt inclusions in andesitic phenocrysts vary in silica contents from 56 to 80wt%. Al2O3, FeO, MgO, CaO decrease and Na2O and K2O increase with increasing SiO2. Many inclusions (about 80%) are dacitic or rhyolitic. However, the compositions of silicic glasses (> 65wt% SiO2) in andesites significantly differ in TiO2, FeO, MgO, CaO, and K2O contents from those in dacites and rhyolites. High-potassium melts (K2O 3.8 - 6.8wt%) with various SiO2 from 51.4 to 77. 2wt% were found in minerals of all volcanoes studied. This indicates a contribution of a component selectively enriched in potassium to magmas of the whole region. A great compositional diversity of melt inclusions in plagioclase phenocrysts from the Bezymyannyi andesites suggests a complex history of plagioclase crystallization and magma evolution in the andesite formation. Melts from different volcanoes strongly vary in volatile contents. The highest H2O contents are found in the melts from Shiveluch (3.0 - 7.2wt%, 4.7wt% on average) and Avachinskii (4.7-4.8wt% ); while those are lower in melts of Kudryavyi (0.1 - 2.6wt%), Dikii Greben, (0.4 - 1.8wt%), and Bezymyannyi (< 1wt%). Chlorine contents are also variable. The lowest values are found in the Bezymyannyi melts (0.09wt% on average), the highest Cl contents are typical of melt inclusions in minerals from the Karymskii andesites (0.26wt% on average). The melts from Avachinskii, Dikii Greben', Kudryavyi, and Shiveluch show intermediate Cl contents (0.13 - 0.20wt% ). The pressure of 350 - 1600 bar determined by CO2 fluid inclusions in plagioclase from the Shiveluch andesites suggests a magma chamber at a depth of 1.5 - 6 km. Concentrations of 17 elements were determined in glasses of melt inclusions in plagioclases from five volcanoes (Avachinskii, Bezymyannyi, Dikii Greben', Kudryavyi, and Shiveluch). The studied melts show similar trace-element patterns with Nb and Ti minima and B, K, Be, and Li maxima. The melts are close to typical island arc magmas by Sr/Y, La/Yb, K/Ti, and Ca/Sr ratios, and have some specific regional geochemical features. REE patterns sensitive to degree of magma differentiation indicate that Kudryavyi magmas are most primitive, while Shiveluch magmas are most evolved.
Keywords: ANDESITE; BASALT; DACITE; FLUID; INCLUSION; KAMCHATKA; MELT; RHYOLITE